Self‐changing behaviour in smoking cessation linked to trait and cognitive impulsivity. (21st August 2017) - Celma‐Merola, Jaume; Abella‐Pons, Francesc; Mata, Fernanda; Pedra‐Pagés, Gerard; Verdejo‐Garcia, Antonio
Abstract: Background and aims: To compare impulsivity, measured using self‐report and cognitive tasks in people who ceased smoking without treatment (self‐changers) with each of the following groups: (i) smoking non‐treatment‐seekers, (ii) people in smoking cessation treatment and currently abstinent and (iii) people in smoking cessation treatment but non‐abstinent. Design: Cross‐sectional, observational study. Setting: The smoking cessation unit of a public general hospital, Hospital de Santa Maria, in Lleida, Spain. All participants were from the hospital's catchment area. Participants: One hundred and twenty participants, classified in four groups: (1) self‐changers ( n  = 30, 21 females, mean age = 41.50 years), (2) non‐treatment‐seekers ( n  = 30, 17 females, mean age = 35.27 years), (3) people in smoking cessation treatment and currently abstinent ( n  = 30, 17 females, mean age = 48.93 years) and (4) people in smoking cessation treatment but non‐abstinent ( n  = 30, 21 females, mean age = 33.70 years). Measurements: The Barratt Impulsiveness Scale, including measures of non‐planning, attentional and motor impulsivity, and two behavioural tasks measuring cognitive inhibition (Stroop test) and choice impulsivity (delay‐discounting task). Confounders included sex, age, education, employment, smoking severity, depression and trait and state anxiety. Findings: Although not on the other three measures, we found significant group differences on trait non‐planning impulsivity and Stroop performance. Self‐changers, compared with non‐treatment‐seekers, had lower non‐planning impulsivity ( P  = 0.018, Cohen's d  = 0.62) and better Stroop performance ( P  = 0.001, Cohen's d  = 0.66). Self‐changers also had better Stroop performance than participants in treatment and currently abstinent ( P  = 0.002, Cohen's d  = 0.85). Conclusions: People who have stopped smoking without treatment appear to have lower non‐planning impulsivity and more effective cognitive inhibition compared with smoking non‐treatment‐seekers, and better cognitive inhibition than people who cease smoking with treatment aid.